Interventions to reduce acute paediatric hospital admissions: a systematic review. Issue 3 (2nd August 2021) - Dick, Smita; MacRae, Clare; McFaul, Claire; Rasul, Usman; Wilson, Philip; Turner, Stephen W
Abstract : Background: Admission rates are rising despite no change to burden of illness, and interventions to reduce unscheduled admission to hospital safely may be justified. Objective: To systematically examine admission prevention strategies and report long-term follow-up of admission prevention initiatives. Data sources: MEDLINE, Embase, OVID SP, PsychINFO, Science Citation Index Expanded/ISI Web of Science, The Cochrane Library from inception to time of writing. Reference lists were hand searched. Study eligibility criteria: Randomised controlled trials and before-and-after studies. Participants: Individuals aged <18 years. Study appraisal and synthesis methods: Studies were independently screened by two reviewers with final screening by a third. Data extraction and the Critical Appraisals Skills Programme checklist completion (for risk of bias assessment) were performed by one reviewer and checked by a second. Results: Twenty-eight studies were included of whom 24 were before-and-after studies and 4 were studies comparing outcomes between non-randomised groups. Interventions included referral pathways, staff reconfiguration, new healthcare facilities and telemedicine. The strongest evidence for admission prevention was seen in asthma-specific referral pathways (n=6) showing 34% (95% CI 28 to 39) reduction, but with evidence of publication bias. Other pathways showed inconsistent results or were insufficient for wider interpretation. Staffing reconfiguration showed reduced admissions in two studies, and shorter length of stay in one. Short stay admission units reduced admissions in three studies. Conclusions and implications: There is little robust evidence to support interventions aimed at preventing paediatric admissions and further research is needed. Abstract : Systematic review of interventions and strategies aimed at preventing hospital admission among children and young people finds limited evidence to support their use.